Exploring Consumers' Readiness And Acceptance Of Beacon Technology - Dr. Dipti Jain; Ms. Shipra Bhutani Uppal; Dr. Sanjeev Kumar Singh (Educational Administration: Theory and Practice, 2024)
Purpose: The main objective of this study was to present a broader framework for evaluating beacon technology adoption and readiness. Prospects for beacons are promising, but given the high failure rate of new product innovation, it is important to assess customers' readiness and desire to adopt this technology. Methodology: To assess beacon technology, this study integrated the technological readiness (TR) and acceptability (TAM) models. Five external factors and five internal variables were modified in this study. Perceived usefulness, perceived ease of use, intention to use, actual usage, and perceived enjoyment were the internal factors, and the five external variables were optimism, innovativeness, insecurity, discomfort, and perceived risk. A collection of data was done using questionnaire and AMOS -24 software was utilized to analyze the collected data on a sample of 534 respondents. Findings: This study's noteworthy findings showed a favorable relationship between technological readiness and the perceptions of beacon technology's usefulness, convenience of use, and enjoyment. Furthermore, intention to use was positively related with beacon technology adoption, but perceived risk negatively related with beacon technology usage. Practical Implications: This study filled a significant void in the field of proximity marketing and beacon technology. Retail managers may use the information in this study to help them plan their approaches to beacon technology and its ramifications. It could specifically direct them in handling risk-related concerns, developing beacon technology value propositions, and endorsing beacon technology as a pleasurable activity. Originality: The study's conclusions provide South Asian merchants with insightful information that they can use to develop more successful retail strategies that will lead to the broad adoption of location-based retail apps.